A randomized controlled trial for effectiveness of zolpidem versus acupressure on sleep in hemodialysis patients having chronic kidney disease–associated pruritus. Issue 31 (August 2018) - Rehman, Inayat Ur; Wu, David Bin-Chia; Ahmed, Raheel; Khan, Nisar Ahmad; Rahman, Aziz Ur; Munib, Syed; Lee, Learn Han; Chan, Kok Gan; Khan, Tahir Mehmood
Abstract: Background: Pruritus adds to the complications of chronic kidney disease (CKD) patient and a well-recognized complication among the CKD patients. Majority of the patients on hemodialysis experience a generalized pruritus and patients reported being moderately to extremely disturbed by at least one of the sleep-related condition. This study aim to investigate the effectiveness of zolpidem 10 mg and acupressure therapy on foot acupoints to improve the sleep quality and overall quality of life among hemodialysis patients suffering from CKD-associated pruritus. Methods: A multicentered, open-label, parallel group, prospective randomized controlled trial among patients suffering from CKD-associated pruritus with sleep disturbance, after randomization into control, and intervention group to be held at North West General Hospital and Research Center Peshawar, Pakistan and Institute of Kidney Diseases Peshawar, Pakistan. Results: The primary outcome is to investigate the effectiveness of zolpidem 10 mg and acupressure therapy on foot acupoints to improve the sleep quality and overall quality of life among hemodialysis patients suffering from CKD-associated pruritus. After baseline assessment by Urdu version of 5D itch scale and Urdu version of Pittsburgh Sleep Quality Index (PSQI) and Urdu EQ-5D 3L, the intervention group will be given zolpidem 10 mg oral tablets and control group with acupressure on both foots on KI-1 acupoints for total of 6 minutes. Assessment will be done at weeks 4 and 8 from baseline by using Urdu version of 5D itch scale and Urdu version of PSQI and Urdu EQ-5D 3L, whereas safety profiling of zolpidem 10 mg tablet at week 6 from baseline and acupressure acceptability at week 6 from baseline. Analysis of covariance will be used to examine the differences in treatment effects between the intervention and control groups. Conclusion: Improvement of sleep quality and quality of life among patients with CKD-associated pruritus requires great importance. This study aims to improve the quality of sleep and quality of life among patients with hemodialysis suffering from CKD-associated pruritus.